Hospital‐initiated post‐discharge medication reviews in Australia: expert opinion on the barriers and enablers to implementation. (6th October 2022) - Angley, Manya; Criddle, Deirdre; Rigby, Deborah; Elliott, Rohan A.; Phillips, Katie; Penm, Jonathan; Sluggett, Janet K.; Gailer, Joy; Thiele, Horst; Page, Amy T.; Pauw, Carly; Gillespie, Sarah; et al.
Abstract: Medication‐related harm can occur during transitions of care. Revised Home Medicines Review (HMR) and Residential Medication Management Review (RMMR) program rules were published in April 2020 which allowed provision for some hospital medical practitioners to refer at‐risk patients for medication review. In turn, the Society of Hospital Pharmacists of Australia's (SHPA's) Transitions of Care and Primary Care Leadership Committee developed a framework to support hospitals facilitating Hospital‐Initiated Medication Reviews (HIMRs) via three pathways: HMR, RMMR, and Hospital Outreach Medication Review. Following the compilation of draft barriers and enablers to implementation of the SHPA HIMR framework, refinement occurred after broad consultation with hospital‐ and primary care‐based pharmacists with transitions of care experience. The finalised list of barriers and enablers can inform broadscale implementation of the SHPA HIMR framework to reduce medication‐related harm when high‐risk patients transition from hospital to primary care and aged care.